On Contraction Properties for Products of Markov Driven Random Matrices - Guivarac’‎h, Y. (Журнал математичної фізики, аналізу, геометрії, 2008)
We describe contraction properties on projective spaces for products ofmatrices governed by Markov chains which satisfy strong mixing conditions.Assuming that the subgroup generated by the corresponding matrices is "large" we show in particular that the top Lyapunov exponent of their product has multiplicity one and we give an exposition of the related results. Mathematics Subject Classification: 37XX, 22D40, 60BXX, 82B44.